Participatory Planning and Gamification: Insights from Hungary - Katinka Tóbiás; Lajos Boros (Land)
Involving citizens in public decision making has become more and more important recently. However, activating citizens is challenging in urban planning, especially in post-socialist countries, such as Hungary, where civil activity is weak, and citizens’ attitudes are characterized by distrust towards decision-makers. The gamification of planning processes aims to address this issue and support a more democratic planning process. Gamification is the application of game-like elements (e.g., rewards, storytelling, feedback, competition, etc.) in non-game contexts, thus transforming them into more engaging and enjoyable activities. This study aims to present how gamification is used in the Hungarian urban planning processes and the obstacles to using gamified practices. The research is based on semi-structured interviews with urban planning experts in major Hungarian cities. Our results show that although decision-makers are open to using participatory approaches and gamification techniques, no clear guidelines and principles support these aspirations. The lack of trust and the apathy of citizens makes participatory planning a challenging task. Furthermore, the lack of resources is an obstacle and motivation at the same time when innovative planning methods are used.